Cardiac magnetic resonance markers of progressive RV dilation and dysfunction after tetralogy of Fallot repair. Issue 21 (14th August 2015) - Wald, Rachel M; Valente, Anne Marie; Gauvreau, Kimberlee; Babu-Narayan, Sonya V; Assenza, Gabriele Egidy; Schreier, Jenna; Gatzoulis, Michael A; Kilner, Philip J; Koyak, Zeliha; Mulder, Barbara; Powell, Andrew J; Geva, Tal
Abstract : Objective: Patients with repaired tetralogy of Fallot (TOF) are followed serially by cardiac magnetic resonance (CMR) for surveillance of RV dilation and dysfunction. We sought to define the prevalence of progressive RV disease and the optimal time interval between CMR evaluations. Methods: Candidates were selected from a multicentre TOF registry and were included if ≥2 CMR studies performed ≥6 months apart were available without interval cardiovascular interventions. Patients with 'disease progression' (defined as increase in RV end-diastolic volume index (RVEDVi) ≥30 mL/m 2, decrease in RVEF ≥10% or decrease in LVEF ≥10%) were compared with those with 'disease non-progression' (defined as RVEDVi increase ≤5 mL/m 2, RVEF decrease ≤3% and LVEF decrease ≤3%). Results: A total of 849 CMR studies in 339 patients (median age at first CMR 23.6 years) were analysed. Over a median interval of 2.2 years between CMR pairs, RVEDVi increased 4±18 mL/m 2 (p<0.001), RV end-systolic volume index increased 3±13 mL/m 2 (p<0.001), RVEF decreased 1%±6% (p=0.02) and LVEF decreased 1%±6% (p=0.001). Disease progression was observed in 15% (n=76) and non-progression in 26% (n=133). There were no significant differences between those with and without progression in baseline demographic, anatomic, ECG, exercise or baseline CMR characteristics. The optimal time interval between CMR studies for detection of progression was a 3-year interval (63% sensitivity, 65% specificity, area under the receiver operating characteristic curve 0.65). Conclusions: Although progressive RV dilation and decline in biventricular systolic function occur at a slow pace in the majority of adults with repaired TOF, 15% of patients experience rapid disease progression. The results of this study support the practice of serial CMR examinations to identify progressive disease at a time interval of up to 3 years.